2023
DOI: 10.1590/1806-9282.20221211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between monocyte to high-density lipoprotein cholesterol ratio and thrombus burden in patients with deep vein thrombosis

Abstract: OBJECTIVE:The purpose of this study was to evaluate monocyte count and high-density lipoprotein cholesterol levels and their ratio (monocyte/ high-density lipoprotein ratio) in patients with deep venous thrombosis as well as to determine whether this ratio at the time of diagnosis can be an indicator of thrombus burden in terms of thrombus location in deep venous thrombosis. METHODS: We retrospectively analyzed the patient's diagnosis of deep venous thrombosis confirmed with venous Doppler ultrasound, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Through a retrospective analysis, Xu Bin-Bin et al [ 26 ] confirmed the independent connection between low plasma HDL-C levels and the development of DVT in patients who had suffered severe fractures. Patients with deep vein thrombosis had a significantly higher monocyte-to-HDL ratio, according to Doğan et al [ 27 ]. Moreover, researchers have looked into how serum albumin affects the development of deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Through a retrospective analysis, Xu Bin-Bin et al [ 26 ] confirmed the independent connection between low plasma HDL-C levels and the development of DVT in patients who had suffered severe fractures. Patients with deep vein thrombosis had a significantly higher monocyte-to-HDL ratio, according to Doğan et al [ 27 ]. Moreover, researchers have looked into how serum albumin affects the development of deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%